Childhood & Adolescence in Anglo-Saxon Literary Culture - Rudolf, Winfried; Irvine, Susan (Susan Elizabeth) (Book collections on Project MUSE., 2018)
After decades of study dominated by adult gender studies, Childhood and Adolescence in Anglo-Saxon Literary Culture rebalances our understanding of family life in the Anglo-Saxon era by reconstructing the lives of medieval children and adolescents through their literary representation.